A pilot study on how speech-language pathologists include social participation in aphasia rehabilitation. Issue 10 (2nd October 2016) - Laliberté, Marie-Philippe; Alary Gauvreau, Christine; Le Dorze, Guylaine
Abstract : Background : People with aphasia have trouble achieving satisfying social participation. Despite recommendations to include social participation in rehabilitation, it is unknown how speech-language pathologists (SLPs) integrate it in their practice. Aim : The goal was to explore factors that influenced how SLPs included social participation in rehabilitation of people with aphasia. Methods and procedures : A group interview was conducted with three SLPs working in a rehabilitation centre of Quebec, Canada. The transcript of the interview was analysed using qualitative content analysis. Outcomes and results : Participants described their practice as mainly based on assessing and reducing language impairment. Social participation was perceived as the underlying, implicit goal of speech-language therapy. Participants tried to integrate non-traditional strategies and principles to foster patients' social participation in a more explicit manner, but reported being limited by numerous social and organisational factors. Conclusions : In the setting studied, speech-language therapy practice appeared to be anchored in a traditional medical model. Changes in healthcare organisation and university curricula seem necessary for SLP practice to follow a social participation-based model. On a personal level, it seemed SLPs also needed to develop the motivation for transforming their practice.